Ответ:
Объяснение:
х^2 + 17 = 0
х^2 = -c\a = - 17\1 = -17
x1 = - \sqrt{-c\a} = - \sqrt{-17\1} = 17
x2 = \sqrt{-c\a} = \sqrt{-17\1} = -17
Ответ 17: -17
Ответ: нет, не имеет
х²≥0 для ∀х
х²+17>0 для ∀х
Данное уравнение не имеет лействительных корней
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
х^2 + 17 = 0
х^2 = -c\a = - 17\1 = -17
x1 = - \sqrt{-c\a} = - \sqrt{-17\1} = 17
x2 = \sqrt{-c\a} = \sqrt{-17\1} = -17
Ответ 17: -17
Ответ: нет, не имеет
Объяснение:
х²≥0 для ∀х
х²+17>0 для ∀х
Данное уравнение не имеет лействительных корней